The Children City Architecture - Nooraddin, Hoshiar (Advances in Social Sciences Research Journal, 2020)
Since the earliest civilizations, the city had been built to fulfil what the adults had considered as society’s needs and by which architectural solutions. This process had continued in history till the 19th century and established the culture of adults’ city architecture. The children had to fit themselves in the adult’s city. It is mainly during the 1960s when new trends in city architecture have introduced new considerations for children by calling for livability in cities. This trend has increased in the 1990s by the sustainable city trends and the present initiatives of Children Friendly City. But studying contemporary cities can raise an important argument that contemporary cities have not developed children architecture. It requires new ways of understanding children’s needs in the city and how can architecture contain these needs. These two components can establish children architecture as a new reality in our cities